The Effect of Intellectual Capital on Financial Performance with Corporate Social Responsibility as Moderating Variable: Studies on Islamic Commercial Banks - Renanta Ivana Nanda Rusmawan; Iwan Setiawan; Ruhadi Ruhadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to determine the influence of Intellectual Capital and the moderating of Corporate Social Responsibility to financial performance of Islamic banks. The data in this study used secondary data using the IB reports for the years 2010-2021. The independent variable used is IC as measured by Human Capital Efficiency, Structural Capital Efficiency, and Capital Employed Efficiency, and Corporate Social Responsibility as moderating variable. While the dependent variable used is ROA and ROE as the measure of financial performance. This study uses multiple linear regression analysis with data panel models. The results showed that IC as measured by HCE has positive and no significant effect, SCE has positive and significant effect, and CEE has negative and significant effect on financial performance. and as a moderating variable, CSR negatively weakens the relationship between HCE and SCE and financial performance, while CSR positively strengthens the relationship between CEE and financial performance.